2005
DOI: 10.1111/j.1365-2591.2004.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of irrigant needle depth in removing bioluminescent bacteria inoculated into instrumented root canals using real‐time imaging in vitro

Abstract: The mechanical efficacy of 6 mL of irrigant in reducing intracanal bacteria was significantly greater when delivered 1 mm compared with 5 mm from WL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
3
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(161 citation statements)
references
References 30 publications
10
135
3
9
Order By: Relevance
“…They determined the correlation between bioluminescent signal and extracted CFUs. This group went on to use this model to study the effect of varying the needle depth during endodontic irrigation [52].…”
Section: Discussionmentioning
confidence: 99%
“…They determined the correlation between bioluminescent signal and extracted CFUs. This group went on to use this model to study the effect of varying the needle depth during endodontic irrigation [52].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the penetration depth of the irrigation needle affects the extrusion of irrigants, with better cleaning when the irrigation needle is placed. 23,24 The 27-gauge sidevented needle tip was inserted passively and never allowed to bind as the irrigant was being deposited into the canal. However, the SAF's hollow design allows for continuous irrigation throughout the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Closed-ended irrigant tips are side-vented and thus create more pressure on the walls of the root canal and improve the hydrodynamic activation of an irrigant and reduce the chance of apical extrusion. This allows the irrigant to reflux and causes more debris to be displaced coronally, while avoiding the inadvertent expression of the irrigant into periapical tissues [6].…”
Section: Needle-tip Designmentioning
confidence: 99%